How do user experiences with different transport modes affect the risk of traffic accidents? From the viewpoint of licence possession status. (February 2017) - Nakai, Hiroshi; Usui, Shinnosuke
Highlights: Awareness of the characteristics of other transport modes can affect road accident risks. We study perspective-taking ability, with the driving licence as a deciding factor. Senior citizen pedestrians without a licence are likely to be involved in more accidents. Those who had a two-wheeler licence have lower left-turn entanglements risks (Japan is left-driving). Educational interventions should encourage users to consider others' perspectives. Abstract: Road accidents between different modes of transport—such as between automobiles and pedestrians, automobiles and bicycles, or automobiles and motorcycles—are frequent. In such cases, it is important to consider the other side's perspective. This involves the ability to correctly judge, for every given situation, how other people on the road perceive their surroundings and what they intend to do next. In this paper, we conduct two types of studies assuming that this kind of ability to consider perspectives is higher when the person is licenced to drive the mode of transport used by the other party. For Study 1, we analysed accidents involving senior citizens between the ages of 65 and 74 years, who collided with automobiles as pedestrians or cyclists (1656 and 3192 cases respectively), in terms of the accident category and type of road at the accident spot. The results indicate that possession or non-possession of a licence was irrelevant for accidents involving cyclists, but for accidents with pedestrians, senior citizens who did not possess a licence are likely to be involved in a greater number of accidents in places that require interaction with automobiles, such as while crossing at crosswalks or at intersections. For Study 2, we reviewed 875 ordinary first-class licence practical test examinees, categorised them according to their licence possession status (motorcycle licence, moped licence, or no licence), and made a category-wise comparison of the test instructor's assessment of their ability to make a left turn. The results showed that those who had a motorcycle or moped licence tended to make a left turn more safely. Thus, the results indicate that experience with different modes of transport is likely to reduce the risk of accidents. These findings may be used to popularise educational interventions encouraging users of various transport modes to consider the perspective of others (i.e. via perspective-taking).